2015
DOI: 10.1007/s12250-015-3583-6
|View full text |Cite
|
Sign up to set email alerts
|

Polyomavirus interaction with the DNA damage response

Abstract: Viruses are obligate intracellular parasites that subvert cellular metabolism and pathways to mediate their own replication-normally at the expense of the host cell. Polyomaviruses are a group of small DNA viruses, which have long been studied as a model for eukaryotic DNA replication. Polyomaviruses manipulate host replication proteins, as well as proteins involved in DNA maintenance and repair, to serve as essential cofactors for productive infection. Moreover, evidence suggests that polyomavirus infection p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…Thus, DDR proteins may be considered common components of VRCs. While some DDR pathways are antagonized by DNA viruses to prevent the DDR from attenuating infection, others are activated by viruses to promote viral processes [8][9][10]124,125]. However, exactly how cellular DNA repair and DNA replication factors are harnessed to promote viral processes is often unclear.…”
Section: The Composition Of Replication Compartmentsmentioning
confidence: 99%
“…Thus, DDR proteins may be considered common components of VRCs. While some DDR pathways are antagonized by DNA viruses to prevent the DDR from attenuating infection, others are activated by viruses to promote viral processes [8][9][10]124,125]. However, exactly how cellular DNA repair and DNA replication factors are harnessed to promote viral processes is often unclear.…”
Section: The Composition Of Replication Compartmentsmentioning
confidence: 99%
“…Together, these oncogenes commandeer the host cell, promote S-phase entry, and induce multiple rounds of viral and host chromatin replication (7). In addition to promoting S phase, all studied PyVs activate the DNA damage response (DDR) during infection, which is required for efficient amplification of the viral genome, production of virions, and protection of the host from severe DNA damage linked to infection (7)(8)(9).…”
mentioning
confidence: 99%
“…Even though many viruses can cause different tumors in animals, only seven of them are linked with human cancers and are presently regard as oncogenic viruses. These viruses include Human Papillomavirus (HPV), Hepatitis B (HBV) and Hepatitis C Virus (HCV) [22], Epstein Barr Virus (EBV) [23], Human Herpesvirus-8 (HHV8) [24], Human T-cell Leukemia Virus (HTLV) [25] and Merkel Cell Polyomavirus (MCPyV) [26]. There are various mechanisms by which these viruses transformed normal cells into tumor cells [27].…”
Section: Oncogenic Viral Infectionsmentioning
confidence: 99%
“…Hepatitis B or C. Epidemiological studies revealed that there is a strong association between HBV with liver cancer [30]. MCPyV can cause Merkel cell tumor [26] and HTLV-1 causes adult T-cell lymphoma. HHV8 (also known as Kaposi's sarcoma-linked Herpesvirus, KSHV) has been dependable for Kaposi's sarcoma generally found in patients with acquired immunodeficiency syndrome (AIDS) [24] (Tables 4 and 5)…”
Section: Oncogenic Viral Infectionsmentioning
confidence: 99%